ANALISIS PENDEKATAN PEMBELAJARAN MENDALAM TERHADAP PENGEMBANGAN KETERAMPILAN MENULIS - Tri Amelia; Rasti Nawanti; Jumraini; Anita Candra Dewi (Berajah Journal, 2026)
This study aims to analyze the application of a deep learning approach in developing writing skills. The deep learning approach emphasizes conceptual understanding, critical thinking, and active student engagement in the learning process. The research employs a qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of deep learning significantly improves students' writing quality in terms of structure, vocabulary, and the ability to develop ideas in a systematic and logical manner. Furthermore, this approach encourages students to become more reflective, creative, and independent in their writing process. Therefore, the deep learning approach can be considered an effective strategy for enhancing writing skills and achieving more meaningful learning outcomes.